2020
DOI: 10.21037/tcr-20-2074
|View full text |Cite
|
Sign up to set email alerts
|

Impact of endometrial sampling technique and biopsy volume on the diagnostic accuracy of endometrial cancer

Abstract: Background: Histotype and tumor grading of endometrial cancer are the most important factors that have to be assessed by preoperative endometrial sampling, and their concordance with the final surgical and definitive histological findings is of paramount importance. We aim to compare histotype and tumor grading concordance of various endometrial sampling techniques (ESTs) and to investigate the role of endometrial volume biopsy.Methods: We performed a retrospective analysis of patients with apparent early stag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…According to the literature, endometrioid adenocarcinomas with more than 50% solid architecture or 6-50% solid architecture and diffuse marked nuclear atypia were classified as HGEEC [14]. Patients with concomitant second primary cancer and patients that did not have primary surgical treatment were excluded from our cohort; similarly, we excluded those patients that received inadequate surgery due to a missed preoperative correct diagnosis [15].…”
Section: Methodsmentioning
confidence: 99%
“…According to the literature, endometrioid adenocarcinomas with more than 50% solid architecture or 6-50% solid architecture and diffuse marked nuclear atypia were classified as HGEEC [14]. Patients with concomitant second primary cancer and patients that did not have primary surgical treatment were excluded from our cohort; similarly, we excluded those patients that received inadequate surgery due to a missed preoperative correct diagnosis [15].…”
Section: Methodsmentioning
confidence: 99%
“…We retrospectively reviewed and analysed the medical records of the patients diagnosed with mixed endometrial carcinoma. The initial diagnosis was made through targeted hysteroscopic biopsy, pipelle endometrial biopsy or endometrial curettage, obtaining as much material as possible, according to our previously published experience [19]. Subsequently, all patients had imaging with magnetic resonance imaging (MRI) and/or a computerized tomography (CT) scan to assess locoregional or systemic spread of the dis-ease.…”
Section: Methodsmentioning
confidence: 99%
“…This inadequacy was even more surprising in consideration of the easily applicability and pragmatic nature of ERAS principles [14]. Minimally invasive surgery, part of the ERAS protocol, was widely implemented in gynaecological surgery unlike of other aspects but the reasons of this lack are not totally clear and are probably deeply rooted in everyday clinical practice [15][16][17]. Different authors investigated and reported problems of non-compliance to ERAS protocol in all the phases.…”
Section: The Compliance To Eras: a General Overview In The Gynaecolog...mentioning
confidence: 99%